The Role of Moderation In Islamic Jurisprudence According To Al-Alusi And His Interpretation As A Model - Muhammad Firdaus; Fitriana Fitriana (Pengertian: Jurnal Pendidikan Indonesia (PJPI), 2026)
This research, in its modest form, attempts to delve into what Al-Alusi explained about the concept of moderation, which is a mainstay in Islamic jurisprudence, through his interpretation titled "Ruh al-Ma'ani fi Tafsir al-Qur'an al-Karim wa al-Sab' al-Mathani." The topic addresses the meaning of moderation, its proofs, and its importance by following Al-Alusi's statements in his interpretation, with the assistance of his other works to understand the fundamentals of his jurisprudential efforts, in accordance with Al-Alusi's method of reasoning, whether based on definitive or speculative evidence. The researcher reached the most important conclusions: they indicate Al-Alusi's interest in the issue of moderation: the balance between religious texts and public interests. This openness allowed Al-Alusi to overcome the strict constraints of traditional interpretations and to deal with different opinions within Islamic sects in a tolerant manner and with a spirit of intellectual flexibility. Al-Alusi sought to avoid extremism in interpretation, as he rejected confining religion to a single rigid interpretation.